Eko-Spritualitas Trinitaris: Mendialogkan Konsep Trinitas dan “Debata Mulajadi Na Bolon” dalam Kerangka Ekoteologis - Josua Gesima Gultom (Collecta: Jurnal Teologi dan Tradisi Kristen, 2024)
This article explores the environmental crisis as not solely a matter of physical degradation, but also as a reflection of a deeper spiritual crisis arising from humanity’s estrangement from the natural world. By engaging in a dialogue between the Christian theological concept of the Trinity and the Batak Toba belief in Debata Mulajadi Na Bolon, this study brings together the spiritual values of these two traditions to offer a unique perspective. Meister Eckhart's interpretation of the Trinity emphasizes a dynamic and reciprocal relationship between God and creation, highlighting God's simultaneous transcendence and immanence within both human life and the natural world. Similarly, Debata Mulajadi Na Bolon is understood as the creator of the universe and its entirety, actively participating in human existence. Both traditions affirm a sacred interconnectedness between humanity, nature, and creation. This article argues that effective environmental action must be rooted in a deep spiritual consciousness that recognizes humans as integral to creation, rather than as separate dominators. By reestablishing this spiritual connection, we can approach the environmental crisis with a more comprehensive, holistic response, where care for nature becomes an essential aspect of spiritual responsibility. Trinitarian Eco-Spirituality, therefore, emerges as a crucial framework for cultivating a renewed consciousness that reveres nature as a living and sacred creation, necessitating its protection and stewardship by humankind.